Methods of Strengthening The “Personal Principle” In Modern Radio Journalism - Ismailova, Klimentina (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study examines the role of the "personal principle" in modern radio journalism, emphasizing the influence of a journalist’s authorial presence in broadcasting. The research aims to analyze methods for enhancing journalistic impact through expressive techniques, personal narratives, and audience engagement strategies. Using a qualitative and analytical approach, the study reviews various radio formats, evaluating the effectiveness of personalized storytelling and vocal techniques. The findings suggest that integrating the journalist's personality into broadcasts enhances listener engagement, enriches content delivery, and strengthens the connection between the journalist and the audience.